Survei Tingkat Minat terhadap Ekstrakurikuler Pramuka pada Siswa SMP Negeri - , Trinovandhi Setyawan; Achmad Afandi; Paulus Rah Adi Pawitra; Yusvidha Ernata; Winarno Winarno (Dewantara : Jurnal Pendidikan Sosial Humaniora, 2026)
The purpose of this study was to determine the level of student interest in extracurricular Scouting activities at SMP Negeri 30 Malang City. This study used a survey given to 31 students. Data were analyzed using descriptive statistics methods that display percentages. The survey results showed that students have a very positive interest and perception of extracurricular Scouting activities. 92% of respondents agreed that Scouting activities at school are voluntary. 93% of students agreed that Scouting participants are more disciplined than students who do not participate in these activities. All respondents (100%) agreed that Scouting teaches perseverance, independence, simple living, and is able to shape and change students’ character for the better. In addition, 100% of respondents disagreed that Scouting activities are boring, and 74% disagreed that they are tiring. 90.4% of students also stated that Scouting activities are mandatory at school. When asked about the possibility of not holding Scouting activities at school, all respondents expressed a negative or disagree attitude, indicating that they consider it important to continue implementing these activities. The research results show that students at SMP Negeri 30 Malang City have a high level of interest in Scouting extracurricular activities. They view Scouting as beneficial for building character, improving discipline, fostering independence, and instilling positive values ​​in their daily lives.